Powieść в Советском союзе не было аддерола Olgi Breininger z perspektywy posthumanizmu - Stryjakowska, Anna (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2019)
The analysis focuses on the novel’s protagonist – a young woman who gets involved in an experiment that is aimed at creating the contemporary Übermensch. It is claimed that the novel can be interpreted from the perspective of posthumanism, as it questions the anthropocentric standpoint, which refers mainly to the intellectual dimension of the human being and its economic efficiency.